Spatial distribution of echinoderms in littoral area of Ambon Island, Eastern Indonesia - ANA SETYASTUTI; WAHYU PURBIANTORO; HADIYANTO HADIYANTO (Biodiversitas Journal of Biological Diversity, 2018)
Setyastuti A, Purbiantoro W, Hadiyanto. 2018. Spatial distribution of echinoderms in littoral area of Ambon Island, Eastern Indonesia. Biodiversitas 19: 1919-1925. Echinoderms samples were collected in Ambon Island as part of the marine resource inventories designed to study the biodiversity of Maluku Archipelago. The purpose of this works was to investigate the abundance and genus richness of echinoderms within the five sampling sites using single transect orthogonal to the coast consisted of 10-quadrat plot of 5x5m, the distance between plots was 10m at each site. Furthermore, this study also aimed to understand the relation of substrate type and community composition within those five sites. The substrate was classified into four types (sea-grass, macro-algae, sand, rocks and/or dead coral) noted by presence/absence mark at each plot. The differences in total abundance and genus richness among those sites were analyzed using an Analysis of Deviance following a Generalized Linear Models (GLMs) fitted by Poisson and log link. However, in term of genus composition, the data were visualized using a Principal Coordination Analysis (PCoA) plots calculated from Bray-Curtis dissimilarity based on the log (x+1) transformed abundance data. A total of 910 individuals of echinoderms belonging to 19 genera was successfully recorded. Total abundance of echinoderms was different significantly among sites (p<0.05). The most abundant echinoderms were collected from Tanjung Tiram, approximately 68.71 individuals/quadrat, which was almost 1.4 times than those in Liang and even 4 times than those in Suli. The genus composition between sites was significantly different (p<0.05). The composition of substrate types among sites was not significantly different (p>0.05), however the composition of substrates correlated significantly with the composition of echinoderms genus (p<0.05, rho=0.36). In conclusion, more complex the substrate variation in an area will affect the diversity and abundance of Echinoderms community therein.